THE GRAND ETHIOPIAN RENAISSANCE DAM AND THE SHIFTING BALANCE OF POWER IN THE HORN OF AFRICA - Ramadhan, Muhammad Fauzan Rizki (Global: Jurnal Politik Internasional, 2024)
This article briefly explains the correlation between Ethiopia’s ambitious GERD project and the potential shift in power distribution in the region known as the Horn of Africa. The GERD (Grand Ethiopian Renaissance Dam) is a hydroelectric dam designed to drive economic growth by harnessing the Nile River as its core. Focusing on a regional-level analysis, this article will examine the relationship between the completion of the project and the shift in power distribution between Egypt as the local status-quo power, and Ethiopia as the regional challenger. Thus, the dramatic transition in regional structure is related to categorizing the Nile River as a finite natural resource. Using the multiple hierarchy model derived from power transition theory, this article sees that Egypt and Ethiopia view the Nile River as their primary national interest. Both countries perceive the reduced access to the river’s water as an existential threat to their sovereignty and safety. Thus, The GERD project becomes an instrument for Ethiopia to enhance its structural position as a challenger to Egyptian hegemony and gain the right to a more equitable water allocation. Thus, the completion of the project could pose a real threat not only to Egypt’s structural position but also to its survival as a state.